2013
DOI: 10.3389/fpsyg.2013.00409
|View full text |Cite
|
Sign up to set email alerts
|

“What about building 7?” A social psychological study of online discussion of 9/11 conspiracy theories

Abstract: Recent research into the psychology of conspiracy belief has highlighted the importance of belief systems in the acceptance or rejection of conspiracy theories. We examined a large sample of conspiracist (pro-conspiracy-theory) and conventionalist (anti-conspiracy-theory) comments on news websites in order to investigate the relative importance of promoting alternative explanations vs. rejecting conventional explanations for events. In accordance with our hypotheses, we found that conspiracist commenters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 44 publications
(67 reference statements)
2
112
1
1
Order By: Relevance
“…While scholars have discussed the view that endorsing conspiracy theories is a source of stigma, empirical evidence supporting it is scarce. Besides the above‐cited work by Wood and Douglas (), Klein, Van der Linden, Pantazi, and Kissine () have shown that US MTurkers consider that a certain number of negative traits, such as “gullible,” “crazy,” “stupid,” etc. apply more to people who believe in conspiracy theories than to people who do not believe in conspiracy theories.…”
Section: The Hypothesis Of Conspiracy Theories As a Social Stigmamentioning
confidence: 98%
See 1 more Smart Citation
“…While scholars have discussed the view that endorsing conspiracy theories is a source of stigma, empirical evidence supporting it is scarce. Besides the above‐cited work by Wood and Douglas (), Klein, Van der Linden, Pantazi, and Kissine () have shown that US MTurkers consider that a certain number of negative traits, such as “gullible,” “crazy,” “stupid,” etc. apply more to people who believe in conspiracy theories than to people who do not believe in conspiracy theories.…”
Section: The Hypothesis Of Conspiracy Theories As a Social Stigmamentioning
confidence: 98%
“…It is anecdotally believed that conspiracy theories have a negative connotation and may thus be a source of stigma for those who endorse them. Indirect support for this view is provided by Wood and Douglas (), who observed that people promoting alternative explanations for events via comments on news websites (referred to as “conspiracists” by the authors) were reluctant to label and let others label their beliefs as “conspiracy theories.” According to these authors, these observations support the recurrent hypothesis of “social stigma” (p. 1) and of “intellectual stigma” (p. 3) attached to conspiracy theories, which supposedly negatively affects the social perception of people who endorse such theories. As the “stigma” hypothesis becomes increasingly popular (see also Harambam & Aupers, ; Wood, ; Wood & Douglas, ), to test it empirically, it is important to draw on theoretical considerations regarding the nature of stigma.…”
mentioning
confidence: 99%
“…More specifically, our instructions give examples of political and social events (e.g., the assassination of President John F. Kennedy) that have been the source of numerous conspiracy theories. As in other research, we deliberately chose not to mention the word "conspiracy theory" (Douglas & Sutton, 2008;Wood & Douglas, 2013), knowing that the term may be negatively connoted (Husting & Orr, 2007). The item specifically asked to what extent people think the authorities frequently hide the truth regarding the real origin of some events.…”
Section: Construction Of the Single-item Conspiracy Belief Scalementioning
confidence: 99%
“…We did so because the authorities are generally those who establish and disseminate the official explanation. Moreover, systematically questioning the official version provided by authorities is a critical feature of belief in conspiracy theories (Keeley, 1999;Wood & Douglas, 2013). Furthermore, the authorities are easily accused of either being involved, infiltrated, or at least manipulated by the conspirators (Melley, 2002).…”
Section: Construction Of the Single-item Conspiracy Belief Scalementioning
confidence: 99%
“…Another study of on-line discussions of 9/11 conspiracy theories [16], a social-psychological one, brought out several observations at the level of the individual. It was found out that conspiracists are more likely to argue against an opposing interpretation and less likely to argue in favor of their own interpretation, while the opposite is true for conventional commenters (defenders of the official report).…”
Section: Observations Common To Both Experiments and Their Relation Wmentioning
confidence: 99%